PENERAPAN KONSEP PSIKOLOGI LINGKUNGAN PADA PUSAT PENDIDIKAN NON FORMAL DI KOTA SURAKARTA - Tiara Annya; Rachmadi Nugroho; Maya Andria Nirawati (ARSITEKTURA, 2017)
One of the cities in Indonesia that has problems with school dropout children due to economic problems is Surakarta City. By 2015, 1.54% of workers in this city are teenagers and as many as 6.08% of the population are unemployed (Ermawati, 2015). In fact, the world has become more open and the competition both in the field of economy and employment becomes increasingly tight. One solution to solve the problem is with non formal education. Non-formal education serves as a substitute or additional education that can increase both academic and life skills. Another problem that arises is how to improve motivation and stimuli in processing learning for those who drop out of school. This can be achieved by applying the concept of environmental psychology to the design of educational facilities. By using the concept of environmental psychology, the learning activities can run effectively and learners become more creative and innovative. Non formal education system provided at this education center are life skills training, pursuing equalization packages and tutoring. Each of these activities has its own support rooms such as theory classrooms, practice spaces, library, studio and auditorium which each room apply the concept of environmental psychology in its design.